Menthol can be safely applied to improve thermal perception during physical exercise: a meta-analysis of randomized controlled trials - Keringer, P.; Farkas, N.; Gede, N.; Hegyi, P.; Rumbus, Z.; Lohinai, Z.; Solymar, M.; Ruksakiet, K.; Varga, G.; Garami, A. (Scientific Reports, 2020)
Menthol is often used as a cold-mimicking substance to allegedly enhance performance during physical activity, however menthol-induced activation of cold-defence responses during exercise can intensify heat accumulation in the body. This meta-analysis aimed at studying the effects of menthol on thermal perception and thermophysiological homeostasis during exercise. PubMed, EMBASE, Cochrane Library, and Google Scholar databases were searched until May 2020. Menthol caused cooler thermal sensation by weighted mean difference (WMD) of - 1.65 (95% CI, - 2.96 to - 0.33) and tended to improve thermal comfort (WMD = 1.42; 95% CI, - 0.13 to 2.96) during physical exercise. However, there was no meaningful difference in sweat production (WMD = - 24.10 ml; 95% CI, - 139.59 to 91.39 ml), deep body temperature (WMD = 0.02 °C; 95% CI, - 0.11 to 0.15 °C), and heart rate (WMD = 2.67 bpm; 95% CI - 0.74 to 6.09 bpm) between the treatment groups. Menthol improved the performance time in certain subgroups, which are discussed. Our findings suggest that different factors, viz., external application, warmer environment, and higher body mass index can improve menthol`s effects on endurance performance, however menthol does not compromise warmth-defence responses during exercise, thus it can be safely applied by athletes from the thermoregulation point of view.